Identification of an in vitro artemisinin-resistant Plasmodium falciparum kelch13 R515K mutant parasite in Senegal - Sene, Seynabou D.; Pouye, Mariama N.; Martins, Rafael Miyazawa; Diallo, Fatoumata; Mangou, Khadidiatou; Bei, Amy K.; Barry, Alioune; Faye, Oumar; Ndiaye, Oumar; Faye, Ousmane; Sall, Amadou A.; Lopez-Rubio, Jose-Juan; et al. (Frontiers in Parasitology, 2023)
The emergence of artemisinin partial resistance (ART-r) in Plasmodium falciparum malaria parasites has substantially compromised the efficacy of antimalarial treatments across southeast Asia (SE Asia). The spread of ART-r within the African continent could jeopardize past progress made in reducing worldwide malaria burden. A clinical index malaria case was identified in Kaolack, Senegal with persistent fever after complete artesunate-amodiaquine (ASAQ) treatment. Fifteen malaria-infected blood samples were collected by Institut Pasteur Dakar’s Senegalese sentinel surveillance system, from different healthcare centers surrounding the index case. We have identified one Plasmodium falciparum clinical isolate carrying R515K mutation in the artemisinin resistance gene PfKelch13. CRISPR-Cas9 genome editing was carried out and transgenic Pf3D7Pfkelch13R515K was tested for in vitro standard Ring-stage Survival Assay (RSA0-3hpi). Gene editing has confirmed that PfKelch13R515K drove increased in vitro RSA0-3hpi value. In this article, we report the functional significance of PfKelch13R515K mutation in an African context.